2015
DOI: 10.1002/pmj.21470
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Company Resources and Capabilities on Global New Product Program Performance

Abstract: Product innovation and the trend to globalization are two important and interrelated dimensions driving business today. In this article, the results of five published research articles on the topic of global new product development (NPD) are summarized to provide an integrated overview of the factors that impact global NPD program performance. The overall conceptual framework is based on three types of literature—NPD, globalization, and organization. The main theoretical approach for establishing relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 87 publications
1
25
0
2
Order By: Relevance
“…Previous studies by Cooper and colleagues show that top performers in IPM use formal portfolio processes (Cooper et al, ). Kleinschmidt, de Brentani, and Salomo () find that formal NPD processes increase the quality of information integration as well as homework and launch activities (see also de Brentani and Kleinschmidt, ). Teller et al () empirically show that formal project portfolio processes increase portfolio transparency and the quality of collaboration, which in turn increase portfolio success.…”
Section: Hypothesesmentioning
confidence: 99%
“…Previous studies by Cooper and colleagues show that top performers in IPM use formal portfolio processes (Cooper et al, ). Kleinschmidt, de Brentani, and Salomo () find that formal NPD processes increase the quality of information integration as well as homework and launch activities (see also de Brentani and Kleinschmidt, ). Teller et al () empirically show that formal project portfolio processes increase portfolio transparency and the quality of collaboration, which in turn increase portfolio success.…”
Section: Hypothesesmentioning
confidence: 99%
“…Similarly, Cooper () found that climate and culture, along with an appetite to invest in innovative projects, and leadership skills, is what drives radical innovation. Yet another study demonstrates that internal resources such as culture and senior management support are what really matters (de Brentani & Kleinschmidt, ). These prior studies complement – rather than contradict – our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Govindarajan & Ramamurti (2011) Mudambi (2011) propose un modèle de la FMN comprenant plusieurs hubs afin de faire face à la diversité des marchés locaux et à la montée en puissance rapide de certains pays émergents. Ces fortes hétérogénéités ont été soulignées notamment du fait de leurs conséquences en termes de politiques de contrôle et de ressources humaines (Jaussaud & Mayrhofer 2013;de Brentani & Kleinschmidt, 2015). Il ressort de ces analyses que les filiales peuvent avoir des contributions variées au processus d'innovation global de la FMN sans qu'elles n'aient été repérées de manière systématique ni mis en correspondance avec les typologies de filiales existantes.…”
Section: Filiales Et Innovation Dans La Fmnunclassified